Numerical and experimental investigation of one-way fluid structure interaction of a vertical cantilever beam in an air stream - Joubert, Eugene Christiaan (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.